2015
DOI: 10.1016/j.jom.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Execution quality: An analysis of fulfillment errors at a retail distribution center

Abstract: a b s t r a c tPurchase orders specify many aspects of a fulfillment process, including item quantity, delivery time, carton labeling, bar coding, electronic data interchange, retail ticketing, and others. These fulfillment terms are instrumental for highly optimized retail supply chains employing automation and techniques such as pack-by-store. When fulfilling a purchase order, a supplier may commit a fulfillment error, i.e., the supplier may fail to adhere to the terms specified by the retailer. The retailer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…That work as well as Craig et al. () investigate the connection between fulfillment errors and inventory policy. Relative to our work, Craig et al.…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…That work as well as Craig et al. () investigate the connection between fulfillment errors and inventory policy. Relative to our work, Craig et al.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The authors also point out the mismatch between common chargeback cost and true cost of correctable fulfillment errors. That work as well as Craig et al (2015b) investigate the connection between fulfillment errors and inventory policy. Relative to our work, Craig et al (2015b) studies a simpler inventory system-one with deterministic demand and single supplier and single retailer-but considers many more dimensions to potential non-compliance including incorrect labeling, documentation, and failure to transit an advance ship notice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Craig et al (2015) found that over half of fulfillment errors related to execution quality. These execution‐quality errors included invalid reference numbers or incorrect labels or tickets (Ma, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fulfillment errors are common in practice. Craig, DeHoratius, Jiang, and Klabjan (2015) find fulfillment errors associated with nearly 7% of the POs of a large retailer. Retailers penalize suppliers for fulfillment errors by issuing chargeback penalties, or chargebacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation